Microlearning in Teaching and Learning Process: A Review - Tira Nur Fitria (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2022)
This study reviews micro-learning including its use, benefits, and limitation. This study is library research. The analysis shows that microlearning can be delivered through video, application, gamification, infographics, and social media. Numerous studies demonstrate the benefits of microlearning that lessons can be delivered in a short amount of time. It can be accessed anytime and anywhere. Microlearning is flexible to accommodate different learning styles and can be customized to students’ needs. With short material, students can choose which material is needed, desired, and relevant. Microlearning help increases students’ retention rates and comprehension levels. If the material is broken down into smaller parts, it is easier for students to remember lessons, and easier for teachers to update content and to know learning outcomes. However, the limitations are that microlearning is not suitable for complex and complicated material, and requires detailed explanation. The learning method is dependent on the learning objectives. If the material is in small parts, it can prevent students from understanding the material in-depth. Educators are required to produce their learning content. However, not all educators have the capacity and time to prepare content. Microlearning strategies are related to the individual qualities of learners, the propensity of teachers to utilize digital technology, and external circumstances such as the availability of learning resources.